2022
DOI: 10.1111/avj.13223
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Coxiella burnetii antibodies in wild deer populations in eastern Australia

Abstract: Coxiella burnetii causes significant reproduction losses in livestock and the disease Q fever in humans. Transmission of C. burnetii is facilitated by the stability of the bacterium in the environment and the susceptibility of a variety of host species to infection. Consequently, inter-species transmission occurs frequently through either direct or indirect contact. Wildlife may represent reservoirs of C. burnetii and could therefore be a source of infection for domestic animals. Understanding the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Q fever is a zoonotic disease caused by an obligatorily intracellular bacterium, Coxiella burnetii [1], and nowadays it is considered endemic worldwide, with the exceptions of New Zealand and Antarctica [2,3]. The disease was firstly referred to a febrile illness observed in abattoir workers in Australia [4,5], and the term Q fever was also adapted in veterinary medicine, despite causing a different clinical course in animals. Although this terminology has been maintained, it has been suggested that coxiellosis may be more appropriate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Q fever is a zoonotic disease caused by an obligatorily intracellular bacterium, Coxiella burnetii [1], and nowadays it is considered endemic worldwide, with the exceptions of New Zealand and Antarctica [2,3]. The disease was firstly referred to a febrile illness observed in abattoir workers in Australia [4,5], and the term Q fever was also adapted in veterinary medicine, despite causing a different clinical course in animals. Although this terminology has been maintained, it has been suggested that coxiellosis may be more appropriate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Even though most of the T. gondii and up to 60% of the C. burnetti infections are usually asymptomatic in humans (5,13,14), these two pathogens are of public health concern. Toxoplasmosis can lead to abortion, important neuromuscular diseases in immunocompromised people and even death (5).…”
Section: Introductionmentioning
confidence: 99%